Development of Jumping Task-Based Student Worksheets to Improve the Critical Thinking Skills of Elementary School Students - Ari Rahayu; Dedi Suwito (Program Doktor Pendidikan FKIP Universitas Lampung, 2025)
This study aims to develop student worksheets based on jumping tasks to improve the critical thinking skills of elementary school students in science practicals on the subject of temperature and heat. The research subjects were 20 fifth-grade students at SDN 01 Sangkaran Bhakti in Way Kanan Regency, Lampung Province. The development stages used the ADDIE model, which has five steps: Analysis, Planning, Development, Implementation, and Evaluation. The field test used a One Group Pretest-Posttest Design, which is a form of pre-experimental research method. This design used one group. The types of data in the study were qualitative and quantitative. The effectiveness test obtained a pretest score of 55.38 in the low category and a posttest score of 80.00 in the high category. The conclusion of the research on the development of jumping task-based worksheets in elementary schools is that jumping task-based worksheets are practical and suitable for use in improving the critical thinking skills of fifth-grade elementary school students.